The polymorphisms of ANXA6 influence head and neck cancer susceptibility in the Chinese Han population - Xiong, Weihong; Li, Zhumei; Zeng, Xiangfa; Cui, Jun; Cheng, Zhiming; Yang, Xiaoying; Ding, Yipeng (Frontiers in Oncology, 2023)
Background: Head and neck cancer (HNC) is the sixth most common malignant tumor worldwide and imposes a serious economic burden on society and individuals. Annexin has been implicated in multiple functions which are essential in HNC development, including cell proliferation, apoptosis, metastasis, and invasion. This study focused on the linkage between ANXA6 variants and HNC susceptibility in Chinese people. Methods: Eight SNPs in ANXA6 from 139 HNC patients and 135 healthy controls were genotyped by the Agena MassARRAY platform. The correlation of SNPs with HNC susceptibility was evaluated using odds ratio and 95% confidence interval calculated by logistic regression using PLINK 1.9. Results: Overall analysis results demonstrated that rs4958897 was correlated with an increased HNC risk (allele: OR = 1.41, p = 0.049; dominant: OR = 1.69, p = 0.039), while rs11960458 was correlated with reduced HNC risk (OR = 0.54, p = 0.030). In age ≤ 53, rs4958897 was related to reduce HNC risk. In males, rs11960458 (OR = 0.50, p = 0.040) and rs13185706 (OR = 0.48, p = 0.043) were protective factors for HNC, but rs4346760 was a risk factor for HNC. Moreover, rs4346760, rs4958897, and rs3762993 were also correlated with increased nasopharyngeal carcinoma risk. Conclusions: Our findings suggest that ANXA6 polymorphisms are linked to the susceptibility to HNC in the Chinese Han population, indicating that ANXA6 may serve as a potential biomarker for HNC prognosis and diagnosis.